Minimally invasive sacroiliac joint fusion using a novel hydroxyapatite-coated screw system improves functional outcomes in patients with sacroiliitis at two year follow-up - Alex Mohit; Torrey Shirk (Interdisciplinary Neurosurgery, 2020)
Purpose: The aim of the present study is to understand the clinical outcomes of a novel hydroxyapatite-coated (HA-coated) titanium screw for surgical treatment of SI joint dysfunction. Background: The mainstay of therapy for disorders of the sacroiliac (SI) joint has been non-operative treatment including activity modification, non-steroidal anti-inflammatory drugs, and physical therapy. SI joint injections provide diagnostic information and occasional durable therapeutic benefit. When these modalities fail, sacroiliac joint fusion may be recommended. Objective: The objective of this study is to describe the clinical outcomes of a novel HA-coated titanium screw for surgical treatment of SI joint dysfunction. Methods: This study is a retrospective Institutional Review Board-exempt chart review of 45 consecutive patients who underwent minimally invasive SI joint fusion with a novel HA-coated screw system. Patients were diagnosed based on North American Spine Society guidelines and evidence-based criteria. Clinical assessments were collected, evaluated, and compared preoperatively and at 3, 6, 12, and 24 months postoperatively. Results: Mean patient age was 68.8 ± 9.4 years, and 61.7% of patients were female. Of the 44 patients, nine underwent bilateral SI joint fusion, while the remaining were unilateral. Screw size ranged from 10 × 35 mm to 10 × 50 mm. Mean preoperative visual analog scale (VAS) SI pain scores decreased significantly by a mean of 6.1 points at 12 months postoperatively (P < 0.001). Mean Oswestry Disability Index (ODI) scores significantly improved from 52.3% at baseline to 11.3% at 3-month follow-up, 11.5% at 6 months, 10.9% at 12 months, and 9.5% at 24 months, leading to improvements of 41.0, 40.8, 41.4, and 42.8 points, respectively. Conclusion: The clinical outcomes of SI joint fusion using an HA-coated screw system to treat sacroiliitis demonstrated significant decreases in VAS SI and ODI scores at 3, 6, 12, and 24 months.